2014 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2014
DOI: 10.1109/smc.2014.6973916
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Particle Swarm Optimization algorithms in Wireless Sensor Network node localization

Abstract: The node localization in Wireless Sensor Network (WSN) presently plays an important role in the field of applications. Particle Swarm Optimization (PSO) algorithm is a typical swarm intelligence method. Researchers propose many PSO variants and try to apply PSO algorithm to the related problems in WSN. This paper focuses on the WSN node localization using PSO algorithm. This paper conducts the experiment simulation, comparison and evaluation work in the node localization using PSO algorithm. The performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Moreover, some studies have shown that bigger inertia weight contributes global search, while smaller inertia weight contributes local search [36]. In [36], the authors use the following equation to express the inertia weight: ω=ωmaxωmaxωminkmax×k, where, ωmax is the initial weight, ωmin is the final weight, kmax is the maximum number of iterations, and k is the current iteration. In this paper, we use the same parameters as [36].…”
Section: Range-based Estimation Algorithm Using Psomentioning
confidence: 99%
“…Moreover, some studies have shown that bigger inertia weight contributes global search, while smaller inertia weight contributes local search [36]. In [36], the authors use the following equation to express the inertia weight: ω=ωmaxωmaxωminkmax×k, where, ωmax is the initial weight, ωmin is the final weight, kmax is the maximum number of iterations, and k is the current iteration. In this paper, we use the same parameters as [36].…”
Section: Range-based Estimation Algorithm Using Psomentioning
confidence: 99%
“…Each particle in DPSO [19] pays full attention to the historical information of all neighboring particles, instead of only focusing on the particle which gets the optimum position in the neighborhood. For particle i , the update function of DPSO is Pij=Pij+c1false(PijPijfalse)+c2Kk=1Kfalse(QkjPijfalse)+c3φ3jKk=1K|QkjQij|j=1,2, where K is the number of neighboring particles of the i th particle.…”
Section: A Survey Of Pso-based Localization Algorithmsmentioning
confidence: 99%
“…TPSO [19] employs time-varying c1, c2, and ω (see Equation (9)) to achieve proper balance between global and local exploitation, where c1=(c1fc1s)ttmax+c1s,1.emc2=(c2fc2s)ttmax+c2s0.166667em, where c1s, c1f, c2s, and c2f are initial and final values of c1 and c2, respectively.…”
Section: A Survey Of Pso-based Localization Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of binary PSO for assisting in localization problem was seen in the work of Zain and Shin [28]. Cao et al [29] have investigated the effectiveness of PSO by comparing with the conventional approach for solving localization problem. Jing et al [30] have presented a similar approach where PSO was found to enhance the clustering operation of WSN.…”
Section: Introductionmentioning
confidence: 99%